Strategi Komunikasi Royale Durian Dalam Menghadapi Krisis Pembuangan Limbah Kulit Durian Melalui Media Sosial Instagram - Dimas Putra Dirmagina; Heidy Arviani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study examines and discusses the communication strategy used by Royale Durian in dealing with the crisis of disposing of durian skin waste through Instagram social media. The research method used is descriptive research with qualitative analysis, this approach is used because the data needed by the author is in the form of information from informants. The data needed in this study were obtained through information from managers and social media officers at Royale Durian. In collecting data, researchers used several techniques, namely observation, interviews, and documentation. The collected data is analyzed by data reduction, data presentation and data verification or drawing conclusions. From the results of the study it can be concluded that the Royale Durian communication strategy has five parts of the strategy used, namely Research, Design, Excute, Measurement or Evaluation, Report. However, there are facts that make it awkward at the plam (planning) and excute (implementation) stages. The obstacle to Royale Durian's communication strategy in dealing with crises is the media factor. Royale Durian also works closely with micro influencers to act as buzzers and hoard negative issues. Keywords: strategy, communication, instagram, buzzer